The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/nmat1809
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias using a spin glass

Abstract: Exchange bias is commonly manifested as the hysteresis-loop shift observed when a ferromagnet is in contact with an antiferromagnet. Here, we report observations of exchange bias with unusual features of a ferromagnet in contact with a spin glass, demonstrating that this is a phenomenon of greater generality. The easily measured properties of the ferromagnet allow access to the internal magnetic degrees of freedom of the glass to which they are coupled. Our results show that a Co/CuMn bilayer system exhibits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
284
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(314 citation statements)
references
References 34 publications
26
284
3
1
Order By: Relevance
“…It can be easily observed the completely different radial structure functions. While that of Co foil shows the well-defined peaks corresponding to the 25 first four Co-Co neighbour distances, the FT of the Co-NPs sample resembles that of Co 3 O 4 oxide, 28,29 with peaks around 1.6, 2.5 and 3 Å, associated with the six Co-O bonds, the four Co-Co bonds (edge-shared CoO 6 octahedra) and the 8 Co-Co bonds (corner-shared CoO 6 octahedra), respectively. 30 However, the contribution of both metallic Co-cores and the CoO thin shell can only be appreciated as sight broadening of the FT peaks and/or shoulder-like features.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be easily observed the completely different radial structure functions. While that of Co foil shows the well-defined peaks corresponding to the 25 first four Co-Co neighbour distances, the FT of the Co-NPs sample resembles that of Co 3 O 4 oxide, 28,29 with peaks around 1.6, 2.5 and 3 Å, associated with the six Co-O bonds, the four Co-Co bonds (edge-shared CoO 6 octahedra) and the 8 Co-Co bonds (corner-shared CoO 6 octahedra), respectively. 30 However, the contribution of both metallic Co-cores and the CoO thin shell can only be appreciated as sight broadening of the FT peaks and/or shoulder-like features.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%
“…[1][2][3] Magnetic NPs can be easily manipulated by external magnetic field gradients and thus, be used for separation of different catalytic solids, hyperthermia 25 treatments or magnetic resonance imaging. [4][5][6] In order to use innovative magnetic NPs for artificial engineering, a systematic characterization is needed to control not only the magnetic properties of an individual particle, but also the collective behavior of an ensemble of interacting magnetic 30 NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research developed by Ali et al on exchange-biased bilayered FM/SG systems revealed that H EB increased monotonically with the SG thickness until it is saturated at a certain value, while H C exhibits a maximum well below the saturation point of H EB . 67 Therefore, in the case of FM/SG interfaces, the degree by which a region of the glass is bound to the FM depends on the characteristics of the spin configuration at the interface. The H EB is provided by the glassy regions that remain largely intact on reversal the FM, whereas those that change on reversal of the FM contribute to H C .…”
mentioning
confidence: 99%
“…10 Within this uncompensated AFM/disordered region description, the moments at intergrain boundaries freeze below T ZFC and align with the uncompensated ones. Thus, analogously to the case of the EB effect observed in oxide nanoparticles, 22,23 here the EB might arise from coupling interactions at the interface between the AFM phases and the spin-glass-like intergrain boundaries.…”
Section: -5mentioning
confidence: 52%